Multi-location evaluation of mungbean (Vigna radiata L.) in Indian climates: Ecophenological dynamics, yield relation, and characterization of locations - Parihar, Ashok K.; Gupta, Sanjeev; Hazra, Kali K.; Lamichaney, Amrit; Sen Gupta, Debjyoti; Singh, Deepak; Kumar, Raju; Singh, Anil K.; Vaishnavi, Rakesh; Jaberson, M. Samuel; Das, Sankar P.; Dev, Jai; et al. (Frontiers in Plant Science, 2022)
Understanding of site-specific changes in crop yields and genotype × environment interaction is crucial, which needs exceptional consideration in the strategic breeding programs. In this study, the multi-location field trial data have been exploited to investigate the impact of environmental conditions on crop phenological dynamics and its influence on the yield of mungbean in different agro-ecological regions of the Indian subcontinent. The present attempt also intended to identify strategic location(s) favoring higher yield and distinctiveness within mungbean genotypes. In the field trial, a total of thirty-four different mungbean genotypes were grown in 39 locations covering north hill zone (n = 4), north-eastern plain zone (n = 6), north-western plain zone (n = 7), central zone (n = 11) and south zone (n = 11). The results revealed that the effect of environment was prominent on both phenological dynamics and productivity of mungbean. The genotype, environment, and genotype × environment accounted for 2.98%, 54.17%, and 29.65% of the total variation in mungbean yield, respectively (p < 0.001) suggesting an oversized significance of site-specific responses of the genotypes. Results demonstrated that a lower temperature than ambient extended both flowering time and maturity period. Linear mixed model results revealed that the changes in phenological events with response to contrasting environments had no direct influence on crop yields for all the genotypes except PM 14-11. Results showed further that the south zone environment caused early flowering and had extended reproductive period which sustained yield along with increased seed size. While, the low rainfall conditions viz., Sriganganagar, New Delhi, Durgapura, and Sagar has substantially condensed the yield irrespective of genotypes. Correlation results and PCA both indicated that rainfall and relative humidity had a significant positive influence on mungbean grain yield. Hence, the present study suggested that the yield potential of mungbean is mostly independent of crop phenological dynamics, rather climatic variables like rainfall or relative humidity has considerable influence on yield. Further, HA-GGE biplot analysis demonstrated Sagar, New Delhi, Sriganganagar, Durgapura, Warangal, Srinagar, Kanpur, and Mohanpur as the high efficiency environments in the selection of new mungbean genotypes with wider adaptability.